Isatuximab plus bortezomib, lenalidomide, and dexamethasone for transplant-ineligible newly diagnosed multiple myeloma patients: a frailty subgroup analysis of the IMROZ trial - Manier, Salomon; Dimopoulos, Meletios-Athanasios; Leleu, Xavier P.; Moreau, Philippe; Cavo, Michele; Goldschmidt, Hartmut; Orlowski, Robert Z.; Tron, Muriel; Tekle, Christina; Brégeault, Marie-France; Shafer, Andrea T.; Beksac, Meral; et al. (Haematologica, 2025)
Patients with multiple myeloma (MM) meeting frailty criteria have worse outcomes than those identified as non-frail. Here, we present a post hoc subgroup analysis of IMROZ, a global, phase III, open-label study investigating isatuximab (Isa) with bortezomib, lenalidomide, and dexamethasone (VRd) followed by Isa-Rd (N=265) versus VRd followed by Rd (N=181) in newly diagnosed transplant-ineligible MM (Ti NDMM) patients using the simplified International Myeloma Working Group (sIMWG) frailty score. Although patients aged >80 years were excluded, there was no exclusion for patients meeting frailty criteria. All patients received standard VRd/Rd dosing; Isa-VRd patients received intravenous Isa (cycle 1, 10 mg/kg once weekly; cycles 2-17, once every 2 weeks; subsequent cycles, once every 4 weeks). Patients with a frailty score of 0/1 were considered nonfrail; scores ≥2 were frail. Using this scoring, 26.7% of patients were frail (26.0% Isa-VRd; 27.6% VRd), and 72.0% non-frail (72.8% Isa-VRd; 70.7% VRd). After a median follow-up of 59.7 months, Isa-VRd significantly improved progression-free survival versus VRd in frail patients (hazard ratio [HR] =0.518; 95% confidence interval [CI]: 0.294-0.912; P=0.0227) and non-frail patients (HR=0.615; 95% CI: 0.419-0.903; P=0.0131). Significantly more frail patients receiving Isa-VRd than VRd achieved minimal residual disease negativity and complete response (odds ratio=3.459; 95% CI: 1.495-8.006; P=0.0030 at 10-5 by next-generation sequencing). Rates of treatment-emergent adverse events leading to definitive discontinuation were similar between both arms regardless of frailty status. This post hoc subgroup analysis of the IMROZ trial demonstrated that Isa-VRd is an effective option with a manageable safety profile for frail patients with Ti NDMM (clinicaltrials gov. Identifier: NCT03319667).